PENGARUH KONFLIK PERAN TERHADAP KEPUASAN KERJA DAN KINERJA PENDETA GEREJA KRISTEN PROTESTAN DI BALI - Maoe, Verry Alexander; Sintaasih, Desak Ketut; Sudibya, Gede Adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
Role conflict can be experienced by many professions that can affect the satisfaction and job performance of the employees in performing their duties and role. This study aims to determine the effect of role conflict toward job satisfaction and performance. The populations in this study are pastor in the Protestant Christian Church in Bali. Sampling was carried out research with saturated or census sampling method in order to get results that has a small error rate and tend to be closer to the true value based on the prescribed criteria, so the sample size of this study as many as 56 Pastors. The research data is primary data obtained from questionnaires distributed throughout the Pastors. Research hypothesis testing is using SEM (Sequential Analysis Modeling) techniques based on covariant Partial Least Square (PLS) with tools SmartPLS application.The results showed that: (1) Role conflict significant negative effect on job performance. (2) Role Conflict and significant negative effect on job satisfaction. (3) Job satisfaction significant positive effect on job performance.
Keywords: Role Conflict, Job satisfaction and Job performance